2020
DOI: 10.1021/acsaem.0c00727
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Preoxidation Treatments on Performances of Pitch-Based Hard Carbons for Sodium-Ion Batteries

Abstract: Recently, sodium-ion batteries have been intensively studied as an alternative to lithium-ion batteries because of the abundance of sodium and its ability, for example, to answer to smart grid energy storage applications. Among all anode materials, carbonaceous materials have shown promising results, particularly hard carbons owing to their high capacity and low insertion voltage (vs. Na + /Na). However, these materials often suffer from their high cost and low initial coulombic efficiency. In this paper, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…It has been reported that preoxidation of carbon precursor could introduce oxygen functional groups to facilitate the crosslinking and interrupt the graphitizing of carbon mixture, resulting in more disordered microstructures, and hence closed pores could be generated in the carbon framework 111 . Even the soft carbon without plateau capacity can show considerable plateau capacity after preoxidation treatment 112–114 . Lu et al 114 preoxidated pitch in the air at 300°C for 3 h and then thermal‐treated it at 1400°C.…”
Section: Sodium Storage Mechanism In Hard Carbon Materialsmentioning
confidence: 99%
“…It has been reported that preoxidation of carbon precursor could introduce oxygen functional groups to facilitate the crosslinking and interrupt the graphitizing of carbon mixture, resulting in more disordered microstructures, and hence closed pores could be generated in the carbon framework 111 . Even the soft carbon without plateau capacity can show considerable plateau capacity after preoxidation treatment 112–114 . Lu et al 114 preoxidated pitch in the air at 300°C for 3 h and then thermal‐treated it at 1400°C.…”
Section: Sodium Storage Mechanism In Hard Carbon Materialsmentioning
confidence: 99%
“…Several materials, such as tin-or antimony-based alloys [11][12][13], metal oxides [14][15][16][17][18][19], organic compounds [20][21][22][23][24], or carbonaceous materials [4,5,8,[25][26][27][28][29][30][31][32], have been studied as negative electrode for SIBs. Among them, hard carbons (HC) turn out to be very promising candidates [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Such materials are able to store sodium ions with a high reversible capacity (between 250 and 300 mAh g -1 ), low working potential (vs. Na + /Na) and good cycling stability [36,37]. Moreover, they are inexpensive and easy to synthesize from many carbonaceous precursors, mainly oxygen-rich molecules and polymers [36] such as, for example, sucrose [5,38,39], glucose [8,26,40], cellulose [6,33,41,42], lignin [2,43], phenolic resins [44][45][46][47][48] or pre-oxidized pitch [34,45,49]. Among all the precursors of hard carbons, those derived from biomass are of great interest lately, such as lignocellulosic biomass and fruit wastes [36,[50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Janot and Hu et al shown that the preoxidation treatment can effectively hinder the graphitization of pitch upon pyrolysis and induce an amorphous microstructure with high Na storage capacity. [ 24 ] Song and Lv et al used CaCO 3 and NaCl as templates to introduce mesoporous structure into the pitch‐derived hard carbon, which can shorten the Na + ion diffusion path and achieve superior electrochemical performance. [ 25,26 ] Whereas, the specific surface area (SSA) is apt to increase with the introduction of defects and pores, thereby reducing the initial Coulombic efficiency (ICE).…”
Section: Introductionmentioning
confidence: 99%